G331(P) Engaging site research staff in meta-planning to improve recruitment to a randomised controlled trial (the CAP-IT trial); a PERUKI study. (May 2019) - Barratt, S; Sturgeon, K; Roland, D; Greenwood-Bibby, R; Ahmad, MZ; Hayman, M; Jackson, P; Lyttle, MD
Abstract : Introduction: Engaging busy clinical staff in research can be challenging, but is vital for successful delivery of large randomised control trials (RCT) and observational studies. We aimed to pool the collective experience of site research nurses regarding obstacles and enablers in a PERUKI multicentre RCT; the CAP-IT Trial (a double blind placebo controlled 2 × 2 factorial non-inferiority trial investigating amoxicillin dose and duration for community acquired pneumonia in young children), to optimise recruitment and enable learning for other studies. Methods: We undertook a meta-planning exercise in which site research nurses for the CAP-IT study participated. Rounds focused on obstacles and enablers, and included (i) individual identification of three of each, (ii) 'top-four' ranking by participants, (iii) identification of themes, and (iv) a further round of ranking. Discussion was facilitated by the CAP-IT trial team. Results: Thirty nurses participated from 21 sites. Three key themes were identified: (i) logistics/resources, (ii) patient availability/eligibility, (iii) training. The largest volume and most highly ranked obstacles encountered were in the logistics/resources theme, including lack of out of hours cover (ranked by 28/30), families' reluctance to wait for study processes (8/30), and lack of clinician engagement (7/30). The training theme contained one key obstacle (GCP training, 13/30), but overcoming this represented the highest ranked enabler (19/30). Other key enablers included study specific training (8/30), clinician enthusiasm (7/30), clinicians introducing the study to families (4/30), close follow up of participants (4/30), providing recruitment packs and simplifying out of hours recruitment processes (6/30 and 4/30 respectively). Conclusions: The greatest obstacle to successful delivery of the CAP-IT study is the ability to recruit participants who attend Emergency Departments out of hours. A number of sites have overcome this and the related obstacles of clinician engagement and study-related discharge delays, through ongoing delivery of study specific and GCP training coupled with streamlining processes and extending research capacity. The identified successes will be further enhanced and shared to overcome remaining obstacles in order to optimise the successful delivery of the CAPIT study, and future studies enrolling participants in acute care environments.